A Relational Account of the Causes of Spatial Firm Mobility - Joris Knoben (European Regional Science Association (ERSA), 2006)
The existing literature on the spatial mobility of firms completely neglects the existence of inter-organizational relations (IORs). This is striking since there is a strong theoretical argument in the literature that firms with a high level of embeddedness in (localized) IORs are very unlikely to relocate. Therefore, the following research question is posed: “To what extent is the level of embeddedness of firms in (localized) innovative inter-organizational relationships of influence on their propensity to relocate?” Based on ordered logit model it is shown empirically that there is a strong spatial lock-in effect of having a high degree centrality.
Keywords: L14; R12; R23; 330; Firm relocation; spatial mobility; propensity to relocate; spatial lock-in; spatial inertia; inter-organizational relationships; embeddedness